Nano-cellulose diaphragm with reversible thermal hole closing performance and preparation method and application of nano-cellulose diaphragm

By combining nanocellulose with thermal reversible materials, combined with dynamic in-situ fermentation and mechanical extrusion processes, lithium battery separators with reversible thermal closure properties were prepared, which solved the melting and shrinking of commercial polyolefin separators at high temperatures and poor absorption of electrolytes. The problem of this has achieved the improvement of the safety and energy density of lithium batteries, and has flame retardant functions.

CN119253195APending Publication Date: 2025-01-03DONGHUA UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411145048.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-20
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Commercial polyolefin separators are prone to melt and shrink at high temperatures, and cannot achieve thermal closure function, resulting in short circuit accidents of lithium batteries; their electrolyte is poor in wetting and absorption, resulting in large internal resistance and low energy density of the battery; modified thermal closure separators cannot The pore structure is restored and cannot be used anymore; the coating modified diaphragm has poor adhesion, which affects the thermal shutdown effect.

Method used

Nanocellulose is used as the separator material, and a composite layer with reversible thermally closed pore properties is formed by composite with thermally reversible material (expanded microspheres with putaway structure). Combined with dynamic in-situ fermentation and mechanical extrusion, the High mechanical properties and thermal stability diaphragms and add flame retardant coatings if necessary.

Benefits of technology

It realizes reversible thermal closing of lithium batteries at high temperatures, avoids short circuit accidents, improves the safety and service life of the battery, reduces resource consumption and environmental pollution, enhances the absorption and ion conduction performance of the electrolyte, and has resistance. Burn function.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119253195A_ABST
    Figure CN119253195A_ABST
Patent Text Reader

Abstract

The invention relates to a nanocellulose diaphragm with reversible thermal hole-closing performance and a preparation method and application thereof, the diaphragm is a single-layer or multi-layer structure composite membrane, and comprises a composite layer with a reversible thermal hole-closing function and a nanocellulose membrane; wherein the composite layer is obtained by in-situ compounding of a thermal reversible material and nanocellulose. Compared with a traditional polyolefin diaphragm and an irreversible thermal closed pore diaphragm, the diaphragm provided by the invention not only has the characteristics of natural three-dimensional nano-network pore structure, good thermal stability, high liquid absorption rate, high ion transmission and conductivity and the like, but also has reversible thermal closed pore thermal runaway prevention and selectable flame retardant functions; the safety of the lithium battery is greatly ensured, and the lithium battery has a good market application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to a nanocellulose diaphragm with reversible thermal closure performance, and a preparation method and application thereof. Background Art

[0002] Lithium batteries are widely used in consumer electronics, energy storage and other fields due to their high energy density, long cycle life and high cost performance, and have gradually become the main power source for new energy electric vehicles. As the main development direction of new energy vehicle power batteries, the safety performance of lithium batteries has always attracted much attention.

[0003] As an important component of lithium batteries, the main function of the separator is not only to allow lithium ions to shuttle to ensure the normal operation of the battery, but also to separate the positive and negative electrodes to prevent short circuits in the battery. Its structure and performance will directly affect the safety performance of the battery. At present, commercial separators are mainly porous membranes such as polyethylene (PE) and polypropylene (PP). This type of separator has good mechanical strength and chemical stability, and can self-close at a certain temperature to prevent short circuits.

[0004] However, commercial polyolefin separators have the following pain points: 1) Polyolefin separators will melt at their melting point (>130℃), causing the micropores through which lithium ions pass to disappear, thus blocking the conduction of lithium ions. This is the so-called thermal shutdown closed-pore effect. However, after this type of separator is thermally closed, not only will the shrunk membrane be unable to return to its normal size after the temperature drops, but the blocked micropores will also be unable to recover and are not reversible, causing the battery to be scrapped and unable to continue to be used. 2) The closed-pore temperature of polyolefin separators must reach their melting point. If the closed-pore temperature is high, the thermal shutdown effect cannot be achieved in time, and the separator will undergo significant thermal shrinkage and lose its shielding function, causing the positive and negative electrode materials inside the battery to come into direct contact, resulting in an internal short circuit, and then safety accidents such as fire or explosion may occur. During the use of the currently widely used commercial thermal closed-cell PP / PE / PP three-layer diaphragm, when the temperature rises and PE melts and closes, the outer layer of PP can still temporarily maintain good mechanical properties, but the melting temperatures of the two are relatively close, and thermal inertia will cause the temperature to rise further, causing PP to melt, shrink or rupture, thereby causing a short circuit, which will still cause safety accidents. 3) The poor wettability of the polyolefin diaphragm makes it impossible for the electrolyte to completely infiltrate the internal pores of the diaphragm, resulting in a high internal resistance of the battery, which directly affects the energy density of the battery and the migration of lithium ions. 4) The raw materials of the polyolefin diaphragm rely on limited fossil energy, but its resources are non-renewable and non-biodegradable, making it difficult to meet the requirements of the sustainable development strategy. On the other hand, the production equipment is complex, which increases the preparation cost of the diaphragm. Therefore, it is urgent to develop new bio-based diaphragm materials with thermal stability, reversible thermal closed-cell function, high electrolyte absorption, low cost and green environmental protection.

[0005] Nanocellulose, as a polymer biomaterial, has made breakthrough progress in the fields of green energy storage such as fuel cells, supercapacitors, and lithium batteries in recent years due to its fine structure, rich surface active groups, excellent mechanical and thermal stability, abundant resources and renewable advantages. Among them, bacterial nanocellulose (BNC) is a microbial source nanocellulose synthesized by bacteria. It has a unique and natural 3D nanofiber network structure, excellent thermal stability and mechanical properties, high porosity, specific surface area and crystallinity, high biodegradability, and can be fermented using biomass resources such as waste crops and wet garbage hydrolysate. It is green, renewable and has low cost. Therefore, as a new energy material, it has great commercial application prospects.

[0006] CN108550766A, CN108878738A and CN 112952295A all disclose a type of composite diaphragm with a thermal shutdown temperature below 130°C. The diaphragm is prepared by coating a low-melting-point polymer microsphere layer on one or both sides of the base film. That is, when the temperature reaches the melting point of the microspheres during battery use, the microspheres melt and block the pores, blocking the lithium ion channels and preventing the continued occurrence of internal short circuits. However, at this time, the thermal shrinkage temperature of the base film has not yet been reached, and the diaphragm remains stable, thereby improving the safety of the battery. However, for this type of diaphragm: 1) the base membrane used in CN108550766A and CN108878738A is still a petroleum-based diaphragm, which has a complex preparation method, a heavy environmental burden and high cost; 2) the hot-melt materials used in CN108550766A, CN108878738A and CN 112952295A are not reversible, and the diaphragm after closing cannot restore its original pore structure and cannot be used again after the battery is thermally shut down; 3) the coating method used in CN108550766A, CN108878738A and CN 112952295A has poor adhesion to the diaphragm, and the hot-melt material will experience "powdering" phenomenon, which directly affects its thermal shutdown effect.

[0007] CN111653716B discloses a diaphragm with reversible thermal shutdown performance obtained by coating reversibly thermally expandable polymer microspheres on a base film or a ceramic-coated base film. This type of diaphragm: 1) The base film selected is still a petroleum-based polyolefin diaphragm, which has a complex preparation method, a heavy environmental burden and high cost; 2) The diaphragm needs to be coated with a ceramic layer to ensure the thermal shrinkage of the polyolefin base film; 3) This coating method still cannot solve the problem of "powder loss" of polymer microspheres, and the microsphere layer and ceramic layer in the diaphragm are both achieved by the coating method.

[0008] Therefore, the above methods do not fundamentally solve the problems of existing diaphragms. Therefore, further in-depth research is needed from aspects such as material source and preparation method to develop high-performance lithium battery diaphragms that meet the requirements of power storage, environmental protection and safety. Summary of the invention

[0009] The main technical problems to be solved by the present invention are: 1) Commercial polyolefin separators have poor thermal stability and are prone to melt and shrink at high temperatures, making them unable to perform the thermal closure function, leading to short circuit accidents; 2) The poor wettability and absorption of polyolefin separators in electrolytes result in large internal resistance of the battery and low energy density; 3) The reversibility problem of modified thermal closure / thermal shutdown separators; 4) The adhesion problem that cannot be overcome by coating modified separators.

[0010] The present invention provides a nanocellulose membrane with reversible thermal occlusion performance, wherein the membrane is a single-layer or multi-layer structure composite membrane, comprising a composite layer with reversible thermal occlusion function and a nanocellulose membrane; wherein the composite layer is obtained by in-situ composite of a thermally reversible material and nanocellulose.

[0011] Preferably, the thermoreversible material is a thermally expandable microsphere having a shell (shell polymer)-core (core liquid) structure and having the function of thermal expansion and contraction.

[0012] Preferably, the material of the shell is at least one of polyethylene, polypropylene, ethylene propylene copolymer, acrylonitrile, methyl methacrylate, polystyrene, butyl acrylate, polyvinylidene chloride, butadiene-styrene-(meth)acrylate copolymer, isophorone diisocyanate, toluene diisocyanate, and diphenylmethane diisocyanate; the material of the core is C5-C9 alkane or cycloalkane.

[0013] Furthermore, the C5-C9 alkane or cycloalkane is n-pentane (C 5 H 12 ), cyclopentane (C 5 H 10 ), n-hexane (C 6 H 14 ), benzene (C 6 H 6 ), cyclohexane (C 6 H 12 ), 2-methylpentane (C 6 H 14 ), 2-methylhexane (C 7 H 16 ), isohexane (C 6 H 14 ), 3-methylpentane (C 6 H 14 ), methylcyclopentane (C 6 H 12 ), n-heptane (C7 H 16 ), methylcyclohexane (C 7 H 14 ), ethylcyclopentane (C 7 H 14 ), toluene (C 7 H 8 ), ethylcyclohexane (C 8 H 16 ), n-octane (C 8 H 18 ), ethylbenzene (C 8 H 10 ), para-xylene (C 8 H 10 ), nonane (C 9 H 20 ) at least one of.

[0014] Preferably, the particle size range of the heat-expandable microspheres is 1-10 μm. The particle size of the heat-expandable microspheres directly affects the uniformity of the material in the nanofiber composite membrane and the functional effect of the composite membrane. When the particle size is greater than 10 μm, due to its large particle size and mass, it is not easy for the fiber to coat the microsphere material during the dynamic drum fermentation process, resulting in uneven material composite, affecting the closed-cell effect. Similarly, if the particle size is too large, even if a dispersant is added, the material cannot be evenly dispersed in the fermentation medium, resulting in uneven composite. If the particle size is too small, the network void structure of the nanofiber will be blocked, affecting the ion transmission performance.

[0015] Preferably, the heat-expandable microspheres include those prepared by in-situ polymerization, spray drying, suspension polymerization, etc., and commercial expandable microspheres, wherein the commercial expandable microspheres can be purchased from Polychem (USA), Sekisui (Japan), EXPANCEL (Sweden), AStrong (China), Zhongke Keyou (China), UMICELL (China), etc.

[0016] The preparation method of the thermoreversible material is specifically as follows: (1) Suspension polymerization method: ① Preparation of the aqueous phase, mixing a certain proportion of sodium dodecyl sulfate, deionized water, sodium hydroxide, sodium chloride and other auxiliary agents, and then stirring at a uniform speed to form a uniform aqueous phase; ② Stirring a certain proportion of monomers, initiators and crosslinking agents at a uniform speed to obtain the oil phase required for suspension polymerization; ③ Add the oil phase liquid to the aqueous phase and stir to fully disperse the oil phase in the aqueous phase. Heat in a water bath and adjust the temperature to a suitable level. After the temperature stabilizes, react for 8 hours to obtain a preliminary product; ④ Gradually add dilute hydrochloric acid to the above product, adjust the pH to 3-4, stir to fully react, repeatedly wash with deionized water several times, filter, and dry in a blast oven at 50°C. (2) Spray drying method: ① Add a certain proportion of deionized water, sodium dodecyl sulfate, other additives and an appropriate amount of core material into the reactor; replace with nitrogen three times, heat to 70°C, and stir evenly; ② Add an appropriate proportion of shell material to the reactor and allow the polymerization reaction to proceed for 6 hours; ③ After the above reaction is completed, cool down, discharge the material, and spray dry at ≤50°C to obtain a thermally reversible material.

[0017] Preferably, the reversible thermal closure temperature of the thermoreversible material is in the range of 60-150° C. A separator with a suitable closure temperature can be selected according to the usage scenario of the battery.

[0018] Preferably, the mass concentration of the thermally reversible material in the composite layer is 0.1%-2%. The concentration of the thermally reversible material directly affects the feasibility of the membrane to produce closed pores in a high temperature environment. A low concentration will not produce a thermal closed pore effect. A high concentration will increase the thickness of the membrane, increase its internal resistance, and also block the pores, thereby weakening its ion transmission performance.

[0019] Preferably, the nanocellulose is at least one of microcrystalline nanocellulose, plant nanocellulose and bacterial nanocellulose.

[0020] Preferably, the diaphragm is a single-layer, double-layer or triple-layer structure. The single-layer structure is a composite membrane of a nanofiber membrane and a thermally reversible material; the two-layer structure is a composite structure of a single-layer composite membrane with a thermally reversible pore-closing function and a pure nanofiber membrane; the three-layer structure is a composite structure of a nanofiber membrane-a composite layer with a reversible thermal pore-closing function-a nanofiber membrane.

[0021] In the single-layer structure, the thermoreversible material is embedded in the nanofibers, and the nanofiber membrane provides a network support skeleton to ensure the mechanical and thermal stability of the diaphragm. The addition of pure nanofiber membranes in the two-layer and three-layer structures further ensures the mechanical properties of the composite membrane diaphragm, which plays a key role in preventing dendrite impurities in lithium batteries from piercing and damaging the diaphragm.

[0022] Other functional materials can be added to the above-mentioned nanocellulose membrane with reversible thermal closure properties to make it have composite functions in addition to thermal closure, which allows for greater freedom and flexibility in continuous product upgrades.

[0023] Furthermore, the diaphragm also includes a flame retardant coating.

[0024] Preferably, the flame retardant used in the flame retardant coating is at least one of a bromine-based flame retardant, a phosphorus-based flame retardant, a nitrogen-based flame retardant, an inorganic flame retardant, and a bio-based flame retardant.

[0025] Preferably, the brominated flame retardant includes at least one of decabromodiphenylethane, brominated epoxy resin, and brominated polystyrene; the phosphorus-based flame retardant includes at least one of red phosphorus masterbatch and diphenyl phosphate; the nitrogen-based flame retardant includes at least one of melamine, melamine cyanuric acid, and melamine phosphate; the inorganic flame retardant includes at least one of aluminum hydroxide and magnesium hydroxide; the bio-based flame retardant includes at least one of cardanol, phytic acid, tannic acid, and chitosan.

[0026] Preferably, the mass concentration of the flame retardant in the flame retardant coating is 0.1-1%.

[0027] The concentration of flame retardant will affect the flame retardant effect and ion conductivity of the diaphragm. Low concentration will lead to poor flame retardant effect, and high concentration coating will block pores and cause the ion conductivity of the diaphragm to decrease, which will directly affect the energy density and service life of the lithium battery.

[0028] Preferably, the thickness of the separator is 4-35 μm.

[0029] The diaphragm that can be prepared by the present invention includes:

[0030] (1) Nanocellulose lithium battery separator with reversible thermal closure function: ① Single-layer structure: composite film of BNC and thermal reversible material (TEM) BT (BNC / TEM), CT (CNC / TEM), FT (CNF / TEM), etc.; ② Two-layer structure: BBT (pure BNC layer-BNC / TEM), CCT (CNC-CNC / TEM), FFT (CNF-CNF / TEM), etc.; ③ Three-layer structure: BBTB (BCN-BNC / TEM-BNC), CCTC (CNC-CNC / TEM-CNC), FFTF (CNF-CNF / TEM-CNF), etc.

[0031] (2) Nanofiber lithium battery separators with reversible thermal closure and flame retardant functions: ① Single-layer structure + flame retardant coating: TABT (TA@BNC / TEM), TACT (TA@CNC / TEM), TAFT (TA@CNF / TEM), etc.; ② Two-layer structure + flame retardant coating: TABBT (TA@BNC-BNC / TEM), TACCT (TA@CNC-CNC / TEM), TAFFT (TA@CNF-CNF / TEM), etc.; ③ Three-layer structure + flame retardant coating: TABBTB (TA@BNC-BNC / TEM-BNC), TACCTC (TA@CNC-CNC / TEM-CNC), TAFFTF (TA@CNF-CNF / TEM-CNF), etc.

[0032] The present invention also provides a method for preparing a nanocellulose membrane with reversible thermal closure performance, comprising the following steps:

[0033] (1) preparing a single-layer or multi-layer composite membrane by static in-situ fermentation, dynamic in-situ horizontal drum fermentation, fiber homogenization filtration or membrane patching;

[0034] (2) The obtained single-layer or multi-layer composite membrane is processed by mechanical extrusion and hot pressing and drying to obtain a nanocellulose membrane with reversible thermal closure performance.

[0035] The static in situ fermentation in step (1) is specifically as follows: an in situ static method is adopted, and the preparation process is a single-layer composite membrane of nanofiber membrane and thermoreversible material in situ fermentation; the two-layer structure is divided into first pure fiber membrane fermentation, and then adding thermoreversible material and fiber to form a second layer of composite layer fermentation; the three-layer structure is based on the two-layer structure and then pure membrane fermentation is carried out; the pure membrane and the composite layer with reversible thermal closure function are fermented for 2-3 days each.

[0036] The dynamic in situ horizontal drum fermentation in step (1) is specifically as follows: a horizontal drum reactor is used to prepare a composite membrane with a 3D nano-network structure, during which: the single-layer structure is prepared by in situ dynamic fermentation of a thermally reversible material and nanofibers; the two-layer structure includes a first-layer pure membrane fermentation and a second-layer composite layer fermentation with a reversible thermal pore-closing function; the three-layer structure is based on the two-layer structure and then undergoes pure membrane fermentation; the process parameters of the pure membrane fermentation are: a rotation speed of 5-8rpm and a fermentation time of 2-3 days; the process parameters of the composite layer fermentation with a reversible thermal pore-closing function are: a rotation speed of 5-20rpm and a fermentation time of 2-3 days.

[0037] The fiber homogenization filtration method in step (1) is specifically as follows: the cultured nanofibers and the nanofibers with the thermoreversible material are homogenized separately. Vacuum filtration can obtain a single-layer composite membrane of the thermoreversible material and the nanofibers; vacuum filtration can obtain a two-layer composite membrane of a pure nanofiber layer and a nanofiber layer with the reversible material; and a three-layer structure is obtained by vacuum filtration based on the two-layer structure to obtain a pure membrane layer.

[0038] The membrane patch in step (1) is specifically: a double-layer structure is obtained by combining a fermented purified bacterial nanofiber membrane with a homogenized filtered single-layer thermoreversible material and a composite membrane of nanofibers; a three-layer structure is obtained by adding a layer of purified bacterial nanofiber membrane to the double-layer structure. The bacterial nanofiber membrane includes commercially available or prepared by static / dynamic methods, and the wet membrane thickness is 1-3 mm.

[0039] The preparation method using static and dynamic in situ fermentation can not only obtain the composite diaphragm by in situ integration, but also control the thickness of the diaphragm by changing the culture time. It is worth noting that the dynamic horizontal drum method can further prepare a more uniform composite membrane, further ensuring the reversible thermal closure function of the diaphragm. At the same time, the BNC-based diaphragm prepared by this method has a higher porosity and stronger liquid absorption, and its mechanical properties are also better than the composite membrane prepared by static fermentation.

[0040] During the preparation process of step (1), 1 wt% to 5 wt% of a dispersant may be added to help disperse the reversible hot-melt material.

[0041] Furthermore, it also includes: immersing the single-layer or multi-layer structure composite film obtained in step (1) into a solution containing a flame retardant to form a flame retardant coating on its surface; then processing the obtained multi-layer structure composite film by mechanical extrusion and hot pressing and drying to obtain a nanofiber lithium battery separator with reversible thermal closure function.

[0042] Preferably, the immersion time in the solution containing the flame retardant is 12-48 hours.

[0043] Preferably, the mechanical extrusion in the above steps is specifically: first extruding at 0.1-0.3 MPa for 5-20 minutes, and then extruding at 0.4-0.6 MPa for 5-20 minutes.

[0044] Preferably, the hot pressing and drying in the above steps is specifically: temperature 70-90° C., time 3-7 days.

[0045] The present invention also provides an application of a nanocellulose diaphragm with reversible thermal closure performance in a liquid lithium battery, a semi-solid lithium battery or an all-solid lithium battery.

[0046] The principle of the present invention is as follows:

[0047] The nanocellulose membrane in the present invention has excellent mechanical properties, providing mechanical support for the single-layer and multi-layer composite membranes and the entire diaphragm, and its thermal stability (250°C, almost no shrinkage) also ensures the dimensional stability of the diaphragm in a high-temperature environment. At the same time, its natural nano-network structure is highly electrolyte-affinity, and has considerable advantages in ensuring lithium ion transmission and reducing internal resistance. The thermoreversible material in the composite layer with reversible thermal pore closure function in the present invention expands under high temperature conditions, which can block the nanopores of the diaphragm and block ion transmission, thereby playing a closed-pore role. After the temperature drops, the expanded material shrinks and restores the nanopore structure of the diaphragm, so that the battery can be used normally, which not only effectively avoids a series of safety accidents, but also greatly improves the service life of the battery and saves resources. The two-layer and three-layer structured diaphragms have more excellent mechanical properties and have stronger advantages in preventing internal dendrites in the battery, other impurities from penetrating the diaphragm, and other destructive forces.

[0048] Beneficial Effects

[0049] (1) Compared with traditional commercial diaphragms, the diaphragms of the present invention can close the pores in a hot environment and block the contact between the positive and negative electrodes, which greatly ensures the safety of the lithium battery. The pore structure of the diaphragm can be restored after the temperature drops to ensure the normal operation of the battery.

[0050] (2) Compared with other thermally closed-cell diaphragms, the closed-cell diaphragms of the present invention are reversible, which ensures the service life of the battery, saves resources, and reduces pollution to the environment.

[0051] (3) Compared with traditional commercial diaphragms, the present invention can also be provided with a flame retardant coating, which can quickly extinguish itself when the battery accidentally burns, and can effectively avoid larger safety accidents.

[0052] (4) Nanocellulose enables the present invention to have better thermal stability, higher specific surface area, liquid absorption performance and ionic conductivity, and a very strong network support skeleton compared to traditional commercial membranes.

[0053] (5) The thickness of the membrane prepared by the dynamic in-situ horizontal drum fermentation, static in-situ fermentation, fiber homogenization filtration or membrane patch method adopted by the present invention is controllable. The composite membrane can be prepared by integrated fermentation, and the preparation method is environmentally friendly and simple. Among them, the composite membrane prepared by the dynamic horizontal drum preparation method has the advantages of uniformity, large porosity, strong mechanical properties, etc.

[0054] (6) The present invention adopts in-situ biosynthesis fermentation technology, abandons the traditional membrane coating modification method, and solves the pain point of "powder loss".

[0055] (7) The nanofiber raw materials used in the present invention are renewable and biodegradable. The fibers can be fermented using waste wheat / rice / corn stalks, pulp waste, sugarcane / soybean residues, etc., with low cost.

[0056] (8) The preparation method adopted by the present invention is green and environmentally friendly, has a continuous and simple process, a short preparation time, low energy consumption, easy operation, and easy large-scale production.

[0057] (9) The diaphragm of the present invention has good application prospects in the fields of liquid lithium batteries, semi-solid lithium batteries and all-solid lithium batteries, and is of great significance to environmental protection, energy recycling, energy storage, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1 The technical roadmap of the nanocellulose separator with reversible thermal closure function prepared by the present invention;

[0059] Figure 2 This is a schematic diagram of the closed-cell principle of the nanocellulose membrane with reversible thermal closed-cell function prepared in the present invention. DETAILED DESCRIPTION

[0060] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0061] Example 1

[0062] This example adopts a static in-situ fermentation method to prepare a single-layer nanocellulose membrane with reversible thermal closure performance. The specific preparation method is as follows:

[0063] (1) The thermoreversible material was prepared by suspension polymerization. Specifically, ① 5 g of sodium hydroxide (NaOH, analytical grade, Sinopharm Group Shanghai Chemical Reagent Co., Ltd., the same as in other embodiments) and 12 g of magnesium chloride hexahydrate (MgCl 2 6H 20, 1Kg, Yingwei Jieji (Shanghai) Trading Co., Ltd., other embodiments are the same) dissolved in 200mL of deionized water and stirred evenly. Transfer the NaOH solution to a three-necked flask, add 0.02g of surfactant (at least one of Tween 20, Tween 80, Tuyile dispersant DS-195, DS-172, DS-194H, cationic surfactant hexadecyl dimethyl ammonium bromide (CTAB), anionic surfactant sodium dodecylbenzene sulfonate (SDBS), non-ionic surfactant polyethylene glycol octylphenyl ether (Triton X-100), other embodiments are the same) and stir evenly. Mix the prepared MgCl 2 The solution was slowly added to the three-necked flask using a peristaltic pump at a constant speed, and the speed was adjusted and mechanically stirred for a period of time to form a uniformly dispersed MgCl 2 Suspension system. Sodium nitrite (NaNO 2 , 95%, 500g, Shanghai Aladdin Biochemical Technology Co., Ltd., other embodiments are the same), sodium chloride (NaCl, ≥99.5%, 500g, Sinopharm Chemical Reagent Co., Ltd., other embodiments are the same), anhydrous ethanol (≥99.5%, 500g, Sinopharm Chemical Reagent Co., Ltd., other embodiments are the same) to form a uniform aqueous phase; ② acrylonitrile (99%, 500g, Shanghai Aladdin Biochemical Technology Co., Ltd., other embodiments are the same), methyl acrylate (98.5%, 500mL, MACKLIN / McKlin, other embodiments are the same), methyl methacrylate (99%, 100 3. The mixture of 1,4-dibutyl methacrylate (98%, 25 g, Merck Chemical Technology (Shanghai) Co., Ltd., the same in other embodiments) and n-hexane (≥97.0%, 500 mL, Sinopharm Chemical Reagent Co., Ltd., the same in other embodiments) was weighed in a ratio of 7:1:2, and mixed with dimethyl acrylate-1,4-dibutyl alcohol (98%, 25 g, Merck Chemical Technology (Shanghai) Co., Ltd., the same in other embodiments), azobisisobutyronitrile (12wt%, 500 mL, Shanghai Aladdin Biochemical Technology Co., Ltd., the same in other embodiments), and n-hexane (≥97.0%, 500 mL, Sinopharm Chemical Reagent Co., Ltd., the same in other embodiments) in a beaker and stirred to form a uniformly mixed oil phase; 4. The oil phase liquid was added into the water phase and stirred to fully disperse the oil phase in the water phase. Heat in a water bath and adjust the temperature to 65°C. After the temperature stabilizes, react for 8 hours to obtain a preliminary product; ④ Gradually add dilute hydrochloric acid (36-38%, 500 mL, Sinopharm Chemical Reagent Co., Ltd., the same as in other embodiments) to the above product, adjust the pH to 3-4, stir to fully react, wash repeatedly with deionized water several times, filter, and dry in a blast oven at 50°C to obtain a thermally reversible material.

[0064] (2) Using Komagataeibacter xylinus ATCC 23770 as the bacterial species, 300 mL of fermentation medium (50 g / L glucose, C6 H 12 O 6 , AR, Sinopharm Group Reagent Co., Ltd.; 5g / L tryptone, BR, Sinopharm Group Reagent Co., Ltd.; 3g / L yeast powder, BR, Sinopharm Group Reagent Co., Ltd., the same as other embodiments) were placed in a 30°C constant temperature incubator for static fermentation for 2-3 days, and the fermentation culture solution (20mL) was taken from the clean bench into a culture dish and cultured at 30°C for 1 day. Subsequently, 20mL of a mixed solution of a thermoreversible material (TEM) and a culture medium prepared with a mass concentration of 0.5%, 1%, and 2% was added (the mixed solution was dispersed for 5-10 minutes with an ultrasonic probe of an ultrasonic crusher before sterilization, and 1wt% of a surfactant could be added to the solution as a dispersant) and static fermented for 2-3 days to obtain S-0.5% BT, S-1% BT, and S-2% BT composite membranes.

[0065] (3) The BT composite membranes of different concentrations were placed in a NaOH solution for purification. After treatment at 80°C for 2-4 hours, they were taken out and rinsed with deionized water until neutral to obtain BPE composite membranes of different concentrations. The purpose of this step was to remove bacterial proteins and residual culture medium adhering to the cellulose membrane to ensure the high purity of bacterial nanocellulose.

[0066] (4) The BPE composite film was extruded by two mechanical extrusions (0.1-0.3 MPa, 5-20 minutes and 0.4-0.6 MPa, 5-20 minutes, the same as in other embodiments), and then placed in an oven at 80° C. and dried on a clamp for 3-7 days to finally obtain S-0.5% BT, S-1% BT, and S-2% BT separators.

[0067] Example 2

[0068] This example adopts a dynamic in-situ horizontal drum fermentation method to prepare a single-layer nanocellulose separator with reversible thermal occlusion performance. The specific preparation method is as follows:

[0069] (1) Heat-expandable microspheres were prepared by spray drying, specifically, ① 500 mL of deionized water, 7.5 g of sodium dodecyl sulfate (98.0%, 50 g, Shanghai MacLean Biochemical Technology Co., Ltd., the same in other embodiments) and 7.5 g of Tween 80 (500 mL, Shanghai Titan Technology Co., Ltd., the same in other embodiments), and 100 g of cyclohexane (≥99.0%, 500 mL, Sinopharm Chemical Reagent Co., Ltd., the same in other embodiments) were added into a reactor. Nitrogen replacement 3 times, heating to 70°C, stirring evenly; ② Add 1,3-butadiene (100mL, Shanghai Titan Technology Co., Ltd., the same as in other embodiments), styrene (99%, 100mL, Shanghai Aladdin Biochemical Technology Co., Ltd., the same as in other embodiments), ethylene glycol dimethacrylate (98%, 100mL, Beijing Huawei Ruike Chemical Technology Co., Ltd., the same as in other embodiments) and 2g ammonium persulfate (≥98.0%, 100g, Sinopharm Chemical Reagent Co., Ltd., the same as in other embodiments) in a ratio of 6:3:1 to the reactor, and polymerize for 6 hours. ③ After the above reaction is completed, cool down, discharge, and spray dry at ≤50°C to obtain a thermally reversible material with a shell of cross-linked styrene-butadiene rubber and a core of cyclohexane.

[0070] (2) Using Komagataeibacter xylinus ATCC 23767 as the strain, 300 mL of fermentation medium was fermented in a clean bench at a rotation speed of 5-8 rpm for 1 day, and then a mixed solution of the thermoreversible material fermentation medium prepared above with a mass concentration of 0.5%, 1%, and 2% was added through a peristaltic pump and continued to be dynamically fermented at a rotation speed of 5-20 rpm for 2-3 days to form a composite membrane of BNC and thermoreversible material: D-0.5% BT, D-1% BT, and D-2% BT.

[0071] (3) The BT composite membranes of different concentrations were placed in a NaOH solution, treated at 80°C for 2-4 hours, taken out, and rinsed with deionized water until neutral to obtain BT composite membranes of different concentrations.

[0072] (4) The BT composite film is extruded by mechanical extrusion, and then placed in an oven at 80°C and dried by hot pressing for 3-7 days to finally obtain D-0.5% BT, D-1% BT, and D-2% BT diaphragms.

[0073] Example 3

[0074] This embodiment adopts the method of fiber homogenate filtration to prepare a single-layer nanocellulose membrane with reversible thermal pore closure performance. The specific preparation method is as follows:

[0075] (1) Using Acetobacter xylinum as the bacterial species, the fermentation medium was in situ static plate fermented in a clean bench for 5-15 days to obtain a BNC membrane. The BCB composite membranes of different concentrations were placed in a sodium hydroxide solution, treated at 80°C for 2-4 hours, then taken out and rinsed with deionized water until neutral to obtain a purified BNC membrane.

[0076] (2) The purified BNC membrane is homogenized to obtain a BNC homogenate.

[0077] (3) Take a homogenate containing 0.025 g of BNC and mix it with 0.05 g, 0.125 g, and 0.25 g of commercial thermoreversible material (the commercial heat-expandable microspheres used in the present invention can be purchased from American Polychem: 120DU15, Japanese Sekisui: EM103 (101), Swedish EXPANCEL: DU series, domestic AStrong: HM-85, domestic Zhongke Keyou, domestic Dongjin UMICELL and other companies, the selected particle size range is 1-10 μm, the other embodiments are the same) respectively, and then vacuum filter to form a film.

[0078] (4) The composite film is extruded by mechanical extrusion, and then placed in an oven at 80°C and dried on a splint for 3-7 days to obtain BT. 1:2 , BT 1:5 , BT 1:10 of the diaphragm.

[0079] Example 4

[0080] This embodiment adopts the method of fiber homogenate filtration to prepare a single-layer nanocellulose membrane with reversible thermal pore closure performance. The specific preparation method is as follows:

[0081] (1) Heat-expandable microspheres were prepared by suspension polymerization. Specifically, ① 5 g NaOH and 12 g MgCl were weighed separately. 2 6H 2 O was dissolved in 200 mL of deionized water and stirred evenly. The NaOH solution was transferred to a three-necked flask, and 0.02 g of surfactant was added and stirred evenly. 2 The solution was slowly added to the three-necked flask using a peristaltic pump at a constant speed, and the speed was adjusted and mechanically stirred for a period of time to form a uniformly dispersed MgCl 2 Suspension system. NaNO 2, NaCl, anhydrous ethanol to form a uniform water phase; ② acrylonitrile, methyl acrylate, and methyl methacrylate were weighed in a ratio of 7:1:2, and mixed with dimethyl acrylate-1,4-dibutyl alcohol, azobisisobutyronitrile, and n-octane (96%, 25mL, Shanghai Aladdin Biochemical Technology Co., Ltd., the same in other embodiments) in a beaker for stirring to form a uniformly mixed oil phase; ③ the oil phase liquid was added to the water phase and stirred to fully disperse the oil phase in the water phase. Heat in a water bath, adjust the temperature to 65°C, and after the temperature stabilizes, react for 8 hours to obtain a preliminary product; ④ dilute hydrochloric acid was gradually added to the above product, the pH was adjusted to 3-4, stirred for sufficient reaction, washed repeatedly with deionized water for several times, filtered, and dried in a blast oven at 50°C to obtain a thermally reversible material.

[0082] (2) A slurry containing 0.025 g of CNC (microcrystalline nanofiber, Science K) was taken and uniformly mixed with 0.05 g, 0.125 g, and 0.25 g of the above-mentioned thermoreversible material, respectively, and then vacuum filtered to form a membrane.

[0083] (3) The composite film is extruded by mechanical extrusion, and then placed in an oven at 80°C and dried on a splint for 3-7 days to obtain CT. 1:2 , CT 1:5 , CT 1:10 of the diaphragm.

[0084] Example 5

[0085] This example uses a static in-situ fermentation method to prepare a double-layer nanocellulose separator with reversible thermal closure performance. The specific preparation method is as follows:

[0086] (1) Thermally expandable microspheres were prepared by spray drying, specifically: ① Add 500 mL of deionized water, 7.5 g of sodium dodecyl sulfate, 7.5 g of Tween 80, and 100 g of cyclohexane to a reactor. Replace with nitrogen three times, heat to 70 °C, and stir evenly. ② Add 1,3-butadiene, styrene, ethylene glycol dimethacrylate, and 2 g of ammonium persulfate in a ratio of 6:3:1 to the reactor, and polymerize for 6 hours. ③ After the above reaction is completed, cool down, discharge, and spray dry at ≤50 °C to obtain a thermally reversible material with a shell of cross-linked styrene-butadiene rubber and a core of cyclohexane.

[0087] (2) Using Komagataeibacter xylinus ATCC 23770 as the bacterial strain, 300 mL of fermentation medium was placed in a 30°C constant temperature incubator for static fermentation for 2-3 days, and the fermentation culture liquid (20 mL) was taken into a culture dish in an ultra-clean workbench and cultured at 30°C for 2 days; then 20 mL of a mixed solution of the thermoreversible material prepared in (1) and the culture medium with a mass concentration of 0.5%, 1%, and 2% was added, and static fermentation was carried out for 2-3 days to obtain S-0.5% BBT, S-1% BBT, and S-2% BBT composite membranes with a two-layer structure.

[0088] (3) The BBT composite membranes of different concentrations were placed in a NaOH solution, treated at 80° C. for 2-4 h, taken out, and rinsed with deionized water until neutral to obtain BBT composite membranes of different concentrations.

[0089] (4) The BBT composite film is extruded by two mechanical extrusions, and then placed in an oven at 80°C and dried by hot pressing for 3-7 days to finally obtain S-0.5% BBT, S-1% BBT, and S-2% BBT separators.

[0090] Example 6

[0091] This example uses a dynamic in-situ horizontal drum fermentation method to prepare a double-layer nanocellulose membrane with reversible thermal occlusion performance. The specific preparation method is as follows:

[0092] (1) Thermally expandable microspheres were prepared by spray drying, specifically, ① 500 mL of deionized water, 7.5 g of sodium dodecyl sulfate, 7.5 g of Tween 80, and 100 g of cyclohexane were added to a reactor. Nitrogen was replaced three times, the temperature was raised to 70°C, and stirred evenly; ② 1,3-butadiene, styrene, ethylene glycol dimethacrylate, and 2 g of ammonium persulfate were added to the reactor in a ratio of 6:3:1, and the polymerization reaction was carried out for 6 hours. ③ After the above reaction was completed, the temperature was lowered, the material was discharged, and spray dried at ≤50°C to obtain a thermally reversible material with a shell of cross-linked styrene-butadiene rubber and a core of cyclohexane.

[0093] (2) Using Komagataeibacter xylinus ATCC 23770 as the strain, 300 mL of fermentation medium was horizontally drum fermented at a rotation speed of 5-8 rpm in an ultra-clean workbench for 2-3 days to obtain a first layer of pure membrane; then, a peristaltic pump was used to add 0.5%, 1%, and 2% of the above-mentioned thermoreversible material and a mixed solution of the fermentation medium at a rotation speed of 5-20 rpm to continue dynamic horizontal drum fermentation for 2-3 days to form a composite membrane of BNC and the thermoreversible material, and a 0.5% BBT, 1% BBT, and 2% BBT composite membrane with a double-layer structure was obtained.

[0094] (3) The BBT composite membranes of different concentrations were placed in a sodium hydroxide solution, treated at 80° C. for 2-4 h, taken out, and rinsed with deionized water until neutral to obtain BBT composite membranes of different concentrations.

[0095] (4) The BBT composite film is extruded by mechanical extrusion, and then placed in an oven at 80°C and dried by hot pressing for 3-7 days to finally obtain D-0.5% BBT, D-1% BBT, and D-2% BBT separators.

[0096] Example 7

[0097] In this embodiment, a double-layer nanocellulose membrane with reversible thermal pore closure is prepared by a fiber homogenate filtration method. The specific preparation method is as follows:

[0098] (1) Using Acetobacter xylinum as the bacterial species, the fermentation medium was in situ static plate fermented in a clean bench for 5-15 days to obtain a BNC membrane. The BNC composite membranes of different concentrations were placed in a sodium hydroxide solution, treated at 80°C for 2-4 hours, then taken out and rinsed with deionized water until neutral to obtain a purified BNC membrane.

[0099] (2) The purified BNC membrane is homogenized to obtain a BNC homogenate.

[0100] (3) A homogenate containing 0.075 g of BNC was vacuum filtered to form a first layer of pure BNC membrane; then a homogenate containing 0.025 g of BNC was mixed with 0.05 g, 0.125 g, and 0.25 g of commercial heat-expandable microspheres, respectively, and then vacuum filtered to form a double-layer composite membrane.

[0101] (1) The composite film is extruded by mechanical extrusion, and then placed in an oven at 80°C and dried on a splint for 3-7 days to obtain BBT. 1:2 , BBT 1:5 , BBT 1:10 of the diaphragm.

[0102] Example 8

[0103] In this embodiment, a double-layer nanocellulose membrane with reversible thermal pore closure is prepared by a fiber homogenate filtration method. The specific preparation method is as follows:

[0104] (1) A homogenate containing 0.075 g of CNC was vacuum filtered to obtain a first layer of pure CNC membrane; a homogenate containing 0.025 g of CNC was uniformly mixed with 0.05 g, 0.125 g, and 0.25 g of commercial heat-expandable microspheres, respectively, and then vacuum filtered on them to obtain a double-layer composite membrane.

[0105] (2) The composite film is extruded by mechanical extrusion, and then placed in an oven at 80°C and dried on a splint for 3-7 days to obtain CCT. 1:2 、CCT 1:5 、CCT 1:10 of the diaphragm.

[0106] Example 9

[0107] This embodiment adopts the membrane patch method to prepare a double-layer nanocellulose separator with reversible thermal closure performance. The specific preparation method is:

[0108] (1) Preparation of heat-expandable microspheres by suspension polymerization: ① weigh 5 g NaOH and 12 g MgCl 2 6H 2 O was dissolved in 200 mL of deionized water and stirred evenly. The NaOH solution was transferred to a three-necked flask, and 0.02 g of surfactant was added and stirred evenly. 2 The solution was slowly added to the three-necked flask using a peristaltic pump at a constant speed, and the speed was adjusted and mechanically stirred for a period of time to form a uniformly dispersed MgCl 2 Suspension system. NaNO 2 , NaCl, anhydrous ethanol to form a uniform water phase; ② acrylonitrile, methyl acrylate, and methyl methacrylate were weighed in a ratio of 7:1:2, and mixed with dimethyl acrylate-1,4-dibutyl alcohol, azobisisobutyronitrile, and n-octane (96%, 25mL, Shanghai Aladdin Biochemical Technology Co., Ltd., the same in other embodiments) in a beaker for stirring to form a uniformly mixed oil phase; ③ the oil phase liquid was added to the water phase and stirred to fully disperse the oil phase in the water phase. Heat in a water bath, adjust the temperature to 65°C, and after the temperature stabilizes, react for 8 hours to obtain a preliminary product; ④ dilute hydrochloric acid was gradually added to the above product, the pH was adjusted to 3-4, stirred for sufficient reaction, washed repeatedly with deionized water for several times, filtered, and dried in a blast oven at 50°C to obtain a thermally reversible material.

[0109] (2) Using Komagataeibacter xylinus ATCC 23770 as the bacterial species, 300 mL of fermentation medium was placed in a 30°C constant temperature incubator for static fermentation for 2-3 days. The fermentation culture solution (20 mL) was taken from the clean bench and placed in culture dishes, one of which was cultured at 30°C for 1 day. Subsequently, 20 mL of a mixed solution of the thermoreversible material prepared in (1) with a mass concentration of 0.5%, 1%, or 2% and culture medium was added and statically fermented for 2-3 days to obtain S-0.5% BT, S-1% BT, and S-2% BT composite membranes. The other was fermented at 30°C for 3-5 days to obtain a BNC membrane.

[0110] (3) The above-mentioned BNC pure membrane and BT composite membrane were placed in a sodium hydroxide solution, treated at 80° C. for 2-4 h, taken out, and rinsed with deionized water until neutral to obtain purified BNC membranes and BT composite membranes with different concentrations.

[0111] (4) The BNC film and BT composite film in (2) are cut into the same size, overlapped in the order of BNC-BT, fixed with a plywood, and hot-pressed and dried for 3-7 days to finally obtain a double-layer 0.5% BBT, 1% BBT, 2% BBT composite membrane.

[0112] Example 10

[0113] This embodiment adopts the membrane patch method to prepare a double-layer nanocellulose separator with reversible thermal closure performance. The specific preparation method is:

[0114] (1) Thermally expandable microspheres were prepared by spray drying, specifically, ① 500 mL of deionized water, 7.5 g of sodium dodecyl sulfate, 7.5 g of Tween 80, and 100 g of cyclohexane were added to a reactor. Nitrogen was replaced three times, the temperature was raised to 70°C, and stirred evenly; ② 1,3-butadiene, styrene, ethylene glycol dimethacrylate, and 2 g of ammonium persulfate were added to the reactor in a ratio of 6:3:1, and the polymerization reaction was carried out for 6 hours. ③ After the above reaction was completed, the temperature was lowered, the material was discharged, and spray dried at ≤50°C to obtain a thermally reversible material with a shell of cross-linked styrene-butadiene rubber and a core of cyclohexane.

[0115] (2) Using Komagataeibacter xylinus ATCC 23767 as the bacterial strain, 300 mL of the fermentation medium was fermented in a clean bench at a rotation speed of 5-8 rpm for 2-5 days to obtain a BNC pure membrane.

[0116] (3) Using Komagataeibacter xylinus ATCC 23767 as the bacterial strain, 300 mL of fermentation medium was fermented in a clean bench at a rotation speed of 5-8 rpm for 1 day, and then a peristaltic pump was added to the mixed solution of the thermoreversible material prepared in (1) and the fermentation medium at a mass concentration of 0.5%, 1%, and 2%. The dynamic horizontal drum fermentation was continued at a rotation speed of 5-20 rpm for 2-3 days to form a composite film of BNC and heat-expandable microspheres: D-0.5% BT, D-1% BT, and D-2% BT.

[0117] (4) The BNC film and BT composite film in (2) and (3) are cut into the same size, overlapped in the order of BNC-BT, fixed with a plywood, and hot-pressed and dried for 3-7 days to finally obtain a double-layer 0.5% BBT, 1% BBT, 2% BBT composite membrane.

[0118] Embodiment 11

[0119] This example uses a static in-situ fermentation method to prepare a three-layer nanocellulose membrane with reversible thermal closure performance. The specific preparation method is:

[0120] (1) Using Komagataeibacter xylinus ATCC 23770 as the bacterial strain, 300 mL of fermentation medium was placed in a 30° C. constant temperature incubator for static fermentation for 2-3 days, and the fermentation culture solution (20 mL) was taken from a clean bench and placed in a culture dish, and cultured at 30° C. for 2 days; then 20 mL of a mixed solution of commercial heat-expandable microspheres with a mass concentration of 0.5%, 1%, and 2% and the culture medium was added, and static fermentation was performed for 2-3 days; finally, 20 mL of fermentation medium was added, and static fermentation was performed for 2-3 days to obtain S-0.5% BBTB, S-1% BBTB, and S-2% BBTB composite membranes with a three-layer structure.

[0121] (2) The BBTB composite membranes of different concentrations were placed in a sodium hydroxide solution, treated at 80° C. for 2-4 h, taken out, and rinsed with deionized water until neutral to obtain BBTB composite membranes of different concentrations.

[0122] (3) The BBTB composite film is extruded by two mechanical extrusions, and then placed in an oven at 80° C. and dried by hot pressing for 3-7 days to finally obtain S-0.5% BBTB, S-1% BBTB, and S-2% BBTB separators.

[0123] Example 12

[0124] This example uses a dynamic in-situ horizontal drum fermentation method to prepare a three-layer nanocellulose membrane with reversible thermal occlusion performance. The specific preparation method is as follows:

[0125] (1) Preparation of heat-expandable microspheres by suspension polymerization: ① Weigh 5 g NaOH and 12 g MgCl 2 6H 2 O was dissolved in 200 mL of deionized water and stirred evenly. The NaOH solution was transferred to a three-necked flask, and 0.02 g of surfactant was added and stirred evenly. 2 The solution was slowly added to the three-necked flask using a peristaltic pump at a constant speed, and the speed was adjusted and mechanically stirred for a period of time to form a uniformly dispersed MgCl 2 Suspension system. NaNO 2, NaCl, anhydrous ethanol to form a uniform water phase; ② acrylonitrile, methyl acrylate, and methyl methacrylate were weighed in a ratio of 7:1:2, and mixed with dimethyl acrylate-1,4-dibutyl alcohol, azobisisobutyronitrile, and n-octane (96%, 25mL, Shanghai Aladdin Biochemical Technology Co., Ltd., the same in other embodiments) in a beaker for stirring to form a uniformly mixed oil phase; ③ the oil phase liquid was added to the water phase and stirred to fully disperse the oil phase in the water phase. Heat in a water bath, adjust the temperature to 65°C, and after the temperature stabilizes, react for 8 hours to obtain a preliminary product; ④ dilute hydrochloric acid was gradually added to the above product, the pH was adjusted to 3-4, stirred for sufficient reaction, washed repeatedly with deionized water for several times, filtered, and dried in a blast oven at 50°C to obtain a thermally reversible material.

[0126] (2) Using Komagataeibacter xylinus ATCC 23767 as the bacterial strain, 300 mL of fermentation medium was fermented in a clean bench at a rotation speed of 5-8 rpm for 2-5 days to obtain a first layer of pure membrane; then, a peristaltic pump was used to add a mixed solution of the thermoreversible material prepared in (1) and the fermentation medium at a mass concentration of 0.5%, 1%, and 2%, and the mixture was continued to be dynamically fermented at a rotation speed of 5-20 rpm for 2-3 days to form a composite layer of BNC and heat-expandable microspheres; finally, a peristaltic pump was used to add 100-200 mL of fermentation medium, and the mixture was fermented at a rotation speed of 5-8 rpm for 2-3 days to obtain a 0.5% BBTB, 1% BBTB, and 2% BBTB composite membrane with a three-layer structure.

[0127] (3) The BBTB composite membranes of different concentrations were placed in a sodium hydroxide solution, treated at 80° C. for 2-4 h, taken out, and rinsed with deionized water until neutral to obtain BBTB composite membranes of different concentrations.

[0128] (4) The BBTB composite film is extruded by mechanical extrusion, and then placed in an oven at 80° C. and dried by hot pressing for 3-7 days to finally obtain D-0.5% BBTB, D-1% BBTB, and D-2% BBTB separators.

[0129] Example 13

[0130] In this embodiment, a three-layer nanocellulose membrane with reversible thermal pore closure is prepared by a fiber homogenate filtration method. The specific preparation method is as follows:

[0131] (1) Using Acetobacter xylinum as the bacterial species, the fermentation medium was in situ static plate fermented in a clean bench for 5-15 days to obtain a BNC membrane. The BCB composite membranes of different concentrations were placed in a sodium hydroxide solution, treated at 80°C for 2-4 hours, then taken out and rinsed with deionized water until neutral to obtain a purified BNC membrane.

[0132] (2) The purified BNC membrane is homogenized to obtain a BNC homogenate.

[0133] (3) A homogenate containing 0.075 g of BNC was vacuum filtered to form a first layer of pure BNC membrane; then a homogenate containing 0.025 g of BNC was mixed with 0.05 g, 0.125 g, and 0.25 g of commercial heat-expandable microspheres, respectively, and then vacuum filtered on them to form membranes; then a homogenate containing 0.075 g of BNC was vacuum filtered on them to form a third layer of pure BNC membrane, thereby obtaining a three-layer composite membrane.

[0134] (2) The composite film is extruded by mechanical extrusion, and then placed in an oven at 80°C and dried on a splint for 3-7 days to obtain BBTB. 1:2 BBTB 1:5 BBTB 1:10 of the diaphragm.

[0135] Embodiment 14

[0136] This embodiment adopts the membrane patch method to prepare three layers of nanocellulose separators with reversible thermal closure performance. The specific preparation method is as follows:

[0137] (1) Using Komagataeibacter xylinus ATCC 23770 as the strain, 300 mL of fermentation medium was placed in a 30°C constant temperature incubator for static fermentation for 2-3 days, and the fermentation culture solution (20 mL) was taken from the clean bench and placed in culture dishes, one of which was cultured at 30°C for 1 day. Subsequently, 20 mL of a mixed solution of commercial heat-expandable microspheres with a mass concentration of 0.5%, 1%, and 2% was added to the culture medium and statically fermented for 2-3 days to obtain S-0.5% BT, S-1% BT, and S-2% BT composite membranes. The other was fermented at 30°C for 3-5 days to obtain a BNC membrane.

[0138] (2) The above-mentioned BNC pure membrane and BT composite membrane were placed in a sodium hydroxide solution, treated at 80° C. for 2-4 hours, then taken out and rinsed with deionized water until neutral to obtain purified BNC membranes and BT composite membranes with different concentrations.

[0139] (3) The BNC film and BT composite film in (2) are cut into the same size, overlapped in the order of BNC-BT-BNC, fixed with a splint, and hot-pressed and dried for 3-7 days to finally obtain a double-layer 0.5% BBTB, 1% BBTB, and 2% BBTB composite membrane.

[0140] Embodiment 15

[0141] In this embodiment, a three-layer nanocellulose membrane with reversible thermal pore closure is prepared by a fiber homogenate filtration method. The specific preparation method is as follows:

[0142] (1) A homogenate containing 0.075 g CNF (Science K) was vacuum filtered to form a first layer of pure CNF membrane; then a homogenate containing 0.025 g CNF was mixed with 0.05 g, 0.125 g, and 0.25 g of commercial heat-expandable microspheres, respectively, and then vacuum filtered on them to form membranes; then a homogenate containing 0.075 g CNF was vacuum filtered on them to form a third layer of pure CNF membrane, thereby obtaining a three-layer composite membrane.

[0143] (3) The composite film is extruded by mechanical extrusion, and then placed in an oven at 80°C and dried on a splint for 3-7 days to obtain FFTF. 1:2 , FFTF 1:5 , FFTF 1:10 of the diaphragm.

[0144] Example 16

[0145] This embodiment adopts the membrane patch method to prepare three layers of nanocellulose separators with reversible thermal closure performance. The specific preparation method is as follows:

[0146] (1) Thermally expandable microspheres were prepared by spray drying, specifically, ① 500 mL of deionized water, 7.5 g of sodium dodecyl sulfate, 7.5 g of Tween 80, and 100 g of cyclohexane were added to a reactor. Nitrogen was replaced three times, the temperature was raised to 70°C, and stirred evenly; ② 1,3-butadiene, styrene, ethylene glycol dimethacrylate, and 2 g of ammonium persulfate were added to the reactor in a ratio of 6:3:1, and the polymerization reaction was carried out for 6 hours. ③ After the above reaction was completed, the temperature was lowered, the material was discharged, and spray dried at ≤50°C to obtain a thermally reversible material with a shell of cross-linked styrene-butadiene rubber and a core of cyclohexane.

[0147] (2) Using Komagataeibacter xylinus ATCC 23767 as the bacterial strain, 300 mL of the fermentation medium was fermented in a clean bench at a rotation speed of 5-8 rpm for 2-5 days to obtain a BNC pure membrane.

[0148] (3) Using Komagataeibacter xylinus ATCC 23767 as the bacterial strain, 300 mL of fermentation medium was fermented in a clean bench at a rotation speed of 5-8 rpm for 1 day, and then a peristaltic pump was added to the mixed solution of the thermoreversible material prepared in (1) and the fermentation medium at a mass concentration of 0.5%, 1%, and 2%. The dynamic horizontal drum fermentation was continued at a rotation speed of 5-20 rpm for 2-3 days to form a composite film of BNC and heat-expandable microspheres: D-0.5% BT, D-1% BT, and D-2% BT.

[0149] (4) The BNC film and BT composite film in (2) and (3) are cut into the same size, overlapped in the order of BNC-BT-BNC, fixed with a splint, and hot-pressed and dried for 3-7 days to finally obtain a double-layer 0.5% BBTB, 1% BBTB, and 2% BBTB composite membrane.

[0150] Embodiment 17

[0151] This example uses a dynamic in-situ horizontal drum fermentation method to prepare a single-layer nanocellulose separator with reversible thermal occlusion performance and flame retardant performance. The specific preparation method is:

[0152] (1) Komagataeibacter xylinus ATCC 23767 was used as the bacterial strain, and 300 mL of fermentation medium was fermented in a clean bench at a rotation speed of 5-8 rpm for 1 day, and then a peristaltic pump was added to a mixed solution of the heat-expandable microspheres prepared above and the fermentation medium at a mass concentration of 0.5%, 1%, and 2%, and the dynamic horizontal drum fermentation was continued at a rotation speed of 5-20 rpm for 2-3 days to form a composite film of BNC and heat-expandable microspheres: D-0.5% BT, D-1% BT, and D-2% BT.

[0153] (2) The BT composite membranes of different concentrations were placed in a NaOH solution, treated at 80°C for 2-4 hours, taken out, and rinsed with deionized water until neutral to obtain BT composite membranes of different concentrations.

[0154] (3) The purified BT composite membranes of different concentrations were immersed in a solution containing 0.5% mass concentration of tannic acid (AR, >98%, Shanghai Yien Chemical Technology Co., Ltd., the same as in other embodiments) for 12-48 hours, and the following D-TA@0.5%BT, D-TA@1%BT, and D-TA@2%BT composite membranes were obtained by solution self-assembly.

[0155] (4) The TABT composite film is extruded by mechanical extrusion, and then placed in an oven at 80°C and dried by hot pressing for 3-7 days to finally obtain D-TA@0.5%BT, D-TA@1%BT, and D-TA@2%BT diaphragms.

[0156] Embodiment 18

[0157] This embodiment adopts a static in-situ fermentation method to prepare a double-layer nanocellulose separator with reversible thermal occlusion performance and flame retardant performance. The specific preparation method is:

[0158] (1) Preparation of heat-expandable microspheres by suspension polymerization: ① weigh 5 g NaOH and 12 g MgCl 2 6H 2O was dissolved in 200 mL of deionized water and stirred evenly. The NaOH solution was transferred to a three-necked flask, and 0.02 g of surfactant was added and stirred evenly. 2 The solution was slowly added to the three-necked flask using a peristaltic pump at a constant speed, and the speed was adjusted and mechanically stirred for a period of time to form a uniformly dispersed MgCl 2 Suspension system. NaNO 2 , NaCl, anhydrous ethanol to form a uniform water phase; ② acrylonitrile, methyl acrylate, and methyl methacrylate were weighed in a ratio of 7:1:2, and mixed with dimethyl acrylate-1,4-dibutyl alcohol, azobisisobutyronitrile, and n-octane (96%, 25mL, Shanghai Aladdin Biochemical Technology Co., Ltd., the same in other embodiments) in a beaker for stirring to form a uniformly mixed oil phase; ③ the oil phase liquid was added to the water phase and stirred to fully disperse the oil phase in the water phase. Heat in a water bath, adjust the temperature to 65°C, and after the temperature stabilizes, react for 8 hours to obtain a preliminary product; ④ dilute hydrochloric acid was gradually added to the above product, the pH was adjusted to 3-4, stirred for sufficient reaction, washed repeatedly with deionized water for several times, filtered, and dried in a blast oven at 50°C to obtain a thermally reversible material.

[0159] (2) Using Komagataeibacter xylinus ATCC 23770 as the bacterial strain, 300 mL of fermentation medium was placed in a 30°C constant temperature incubator for static fermentation for 2-3 days, and the fermentation culture liquid (20 mL) was taken into a culture dish in an ultra-clean workbench and cultured at 30°C for 2 days; then 20 mL of a mixed solution of the thermoreversible material prepared in (1) and the culture medium with a mass concentration of 0.5%, 1%, and 2% was added, and static fermentation was carried out for 2-3 days to obtain S-0.5% BBT, S-1% BBT, and S-2% BBT composite membranes with a two-layer structure.

[0160] (3) The BBT composite membranes of different concentrations were placed in a NaOH solution, treated at 80° C. for 2-4 h, taken out, and rinsed with deionized water until neutral to obtain BBT composite membranes of different concentrations.

[0161] (4) The purified BBT composite membranes of different concentrations were immersed in a solution containing 0.5% chitosan (deacetylation degree ≥ 95%, viscosity 100-200 mPa.s, Aladdin Reagent (Shanghai) Co., Ltd., the same as other embodiments) for 12-48 h, and the following D-CS@0.5%BBT, D-CS@1%BBT, and D-CS@2%BBT composite membranes were obtained by solution self-assembly.

[0162] (5) The CS@BBT composite film was extruded by two mechanical extrusions, and then placed in an oven at 80°C and dried by hot pressing for 3-7 days to finally obtain S-CS@0.5%BBT, S-CS@1%BBT, and S-CS@2%BBT separators.

[0163] Embodiment 19

[0164] This embodiment adopts the method of dynamic horizontal drum fermentation to prepare a three-layer nanocellulose membrane with reversible thermal closed-cell performance and flame retardant performance. The specific preparation method is as follows:

[0165] (1) Komagataeibacter xylinus ATCC 23767 is used as the bacterial species, and 300 mL of fermentation medium is fermented in a clean bench at a rotation speed of 5-8 rpm for 2-5 days to obtain a first layer of pure membrane; then, a commercial heat-expandable microsphere with a mass concentration of 0.5%, 1%, or 2% is added to a mixed solution of the fermentation medium by a peristaltic pump, and the solution is continuously fermented in a dynamic horizontal drum at a rotation speed of 5-20 rpm for 2-3 days to form a composite layer of BNC and heat-expandable microspheres; finally, 100-200 mL of fermentation medium is added by a peristaltic pump, and the solution is fermented in a horizontal drum at a rotation speed of 5-8 rpm for 2-3 days to obtain a 0.5% BBTB, 1% BBTB, or 2% BBTB composite membrane with a three-layer structure.

[0166] (2) The BBTB composite membranes of different concentrations were placed in a sodium hydroxide solution, treated at 80° C. for 2-4 h, taken out, and rinsed with deionized water until neutral to obtain BBTB composite membranes of different concentrations.

[0167] (3) The purified BBTB composite membranes of different concentrations were immersed in a solution containing phytic acid (PA, ≥90%, Shanghai MacLean Biochemical Technology Co., Ltd., the same as in other embodiments) with a mass concentration of 0.5% for 12-48 hours, and the following D-PA@0.5%BBTB, D-PA@1%BBTB, and D-PA@2%BBTB composite membranes were obtained by solution self-assembly method:

[0168] (4) The PA@BBTB composite film is extruded by mechanical extrusion, and then placed in an oven at 80°C and dried by hot pressing for 3-7 days to finally obtain D-PA@0.5%BBTB, D-PA@1%BBTB, and D-PA@2%BBTB diaphragms.

[0169] Embodiment 20

[0170] In this embodiment, a three-layer nanocellulose membrane with reversible thermal closure and flame retardant properties is prepared by a fiber homogenate filtration method. The specific preparation method is as follows:

[0171] (1) Using Acetobacter xylinum as the bacterial species, the fermentation medium was in situ static plate fermented in a clean bench for 5-15 days to obtain a BNC membrane. The BCB composite membranes of different concentrations were placed in a sodium hydroxide solution, treated at 80°C for 2-4 hours, then taken out and rinsed with deionized water until neutral to obtain a purified BNC membrane.

[0172] (2) The purified BNC membrane is homogenized to obtain a BNC homogenate.

[0173] (3) A homogenate containing 0.075 g of BNC and 0.5 g of tannic acid were vacuum filtered to form a first layer of pure TA@BNC membrane; then a homogenate containing 0.025 g of BNC and 0.5 g of tannic acid were mixed with 0.05 g, 0.125 g, and 0.25 g of commercial heat-expandable microspheres, respectively, and then vacuum filtered on them to form membranes; then a homogenate containing 0.075 g of BNC and 0.5 g of tannic acid were vacuum filtered on them to form a third layer of TA@BNC membrane, thereby obtaining a three-layer composite membrane.

[0174] (2) The composite film is extruded by mechanical extrusion, and then placed in an oven at 80°C and dried on a splint for 3-7 days to obtain TA@BBTB. 1:2 、TA@BBTB 1:5 、TA@BBTB 1:10 of the diaphragm.

[0175] Embodiment 21

[0176] This embodiment adopts the membrane patch method to prepare three layers of nanocellulose separators with reversible thermal closure performance and flame retardant performance. The specific preparation method is as follows:

[0177] (1) Thermally expandable microspheres were prepared by spray drying, specifically, ① 500 mL of deionized water, 7.5 g of sodium dodecyl sulfate, 7.5 g of Tween 80, and 100 g of cyclohexane were added to a reactor. Nitrogen was replaced three times, the temperature was raised to 70°C, and stirred evenly; ② 1,3-butadiene, styrene, ethylene glycol dimethacrylate, and 2 g of ammonium persulfate were added to the reactor in a ratio of 6:3:1, and the polymerization reaction was carried out for 6 hours. ③ After the above reaction was completed, the temperature was lowered, the material was discharged, and spray dried at ≤50°C to obtain a thermally reversible material with a shell of cross-linked styrene-butadiene rubber and a core of cyclohexane.

[0178] (2) Using Komagataeibacter xylinus ATCC 23767 as the bacterial strain, 300 mL of the fermentation medium was fermented in a clean bench at a rotation speed of 5-8 rpm for 2-5 days to obtain a BNC pure membrane.

[0179] (3) Using Komagataeibacter xylinus ATCC 23767 as the bacterial strain, 300 mL of fermentation medium was fermented in a clean bench at a rotation speed of 5-8 rpm for 1 day, and then a peristaltic pump was added to the mixed solution of the thermoreversible material prepared in (1) and the fermentation medium at a mass concentration of 0.5%, 1%, and 2%. The dynamic horizontal drum fermentation was continued at a rotation speed of 5-20 rpm for 2-3 days to form a composite film of BNC and heat-expandable microspheres: D-0.5% BT, D-1% BT, and D-2% BT.

[0180] (4) The BNC film and BT composite film in (2) and (3) are immersed in a chitosan solution containing a mass concentration of 0.5% for 12-48 hours to obtain CS@BNC and CS@BT composite films through a solution self-assembly method.

[0181] (5) The CS@BNC and CS@BT composite membranes in (4) were cut into the same size, overlapped in the order of CS@BNC-CS@BT-CS@BNC, fixed with a splint, and hot-pressed and dried for 3-7 days to finally obtain double-layer CS@0.5%BBTB, CS@1%BBTB, and CS@2%BBTB composite membranes.

[0182] Comparative Example 1

[0183] According to the preparation method of lithium battery separator described in Chinese patent CN 112952295 A:

[0184] (1) paraffin oil and polyethylene were mixed in a mass ratio of m (paraffin oil): m (polyolefin) = 1000:4, heated to 140° C. to dissolve, and stirred for 1 h to mix evenly;

[0185] (2) cooling the solution obtained in step (1) by 120° C., adding n-octane (GC, >99%, Shanghai MacLean Biochemical Technology Co., Ltd., the same below), and stirring evenly;

[0186] (3) coating the mixture obtained in step (2) on a cellulose porous membrane with a thickness of 20 μm, and then placing it in a constant temperature box at 110° C. for 1 hour, taking it out and cooling it at -10° C. to obtain a composite membrane containing paraffin oil and n-octane;

[0187] (4) immersing the composite membrane obtained in step (3) in n-hexane (AR, ≥97.0%, Sinopharm Chemical Reagent Co., Ltd., the same below), extracting n-octane and paraffin oil therein, repeating the extraction 3 times, each extraction for 1 hour, to obtain a composite membrane containing only n-hexane as the solvent;

[0188] (5) The composite membrane obtained in step (4) is placed in a constant temperature oven and baked at 70° C. for 10 h to remove the n-hexane therein, thereby obtaining a polyethylene-cellulose composite membrane.

[0189] Comparative Example 2

[0190] According to the preparation method of lithium battery separator described in Chinese patent CN 111653716B:

[0191] (1) Deionized water (600 g), surfactant (7.5 g) and cyclohexane (100 g) were added to a reactor, and the temperature was raised to 70°C after nitrogen replacement for 3 times. Three monomers, 1,3-butadiene (189 g), styrene (81 g), and ethylene glycol dimethacrylate (30 g) and 2.4 g ammonium persulfate as an initiator were added to carry out polymerization reaction. After the reaction was kept warm for 6 hours, the temperature was lowered and the material was discharged. The thermally expandable microspheres were obtained by spray drying.

[0192] (2) Alumina powder (500 g, Shanghai Yien Chemical Technology Co., Ltd.), sodium polyacrylate aqueous solution (50% aqueous solution, 100 mL, Shanghai Aladdin Biochemical Technology Co., Ltd.), and acrylonitrile copolymer binder (500 g, Shanghai Aladdin Biochemical Technology Co., Ltd.) were added into a stirrer in a mass ratio of 97:0.7:6.3, and then deionized water was added to mix the slurry and stir, and the solid content was adjusted to 15% to obtain a coating ceramic slurry.

[0193] (3) The microspheres, sodium polyacrylate aqueous solution, and styrene-butadiene rubber binder (500 g, Shanghai Aladdin Biochemical Technology Co., Ltd.) in (1) were added to a stirrer in a mass ratio of 90:0.5:9.5, and then deionized water was added to mix the slurry and stir, and the solid content was adjusted to 15% to obtain a coating heat-expandable microsphere slurry.

[0194] (4) The obtained coated ceramic slurry is coated on one side of the polyethylene base film with a coating thickness of 3 μm. After the ceramic coating is dried, a ceramic PE separator is obtained.

[0195] (5) The obtained heat-expandable microsphere slurry is coated on the other side of the ceramic PE diaphragm with a coating thickness of 1 μm. After drying, a composite diaphragm is obtained.

[0196] Comparative Example 3

[0197] According to the preparation method of lithium battery separator described in Chinese patent CN 114976487B:

[0198] (1) 2.5 mL of acetic acid and 60 mL of deionized water were weighed and placed in a beaker and stirred for 30 min. 6 g of pseudo-boehmite (500 g, Shanghai Yien Chemical Technology Co., Ltd.) was weighed and placed in an acetic acid solution (>95%, 10 g, Shanghai Yuanye Biotechnology Co., Ltd.), and stirred and dispersed at 300 r / min for 30 min. The resulting mixture was placed in a reactor and hydrothermally reacted at 220°C for 16 h. The resulting product was centrifuged at 9000 r / min for 10 min and repeatedly washed with ethanol and deionized water three times. The washed product was dried at 100°C for 12 h to obtain boehmite nanocrystals.

[0199] (2) Weigh 1.4 g of polyacrylonitrile and 10 g of N,N-dimethylacetamide, and then mix and stir for 1 hour to obtain a solution; weigh 0.42 g of the prepared boehmite nanocrystals, put them into the polyacrylonitrile solution, stir and disperse them at a stirring speed of 300 r / min, stir for 1 hour, and then ultrasonically disperse them for 30 minutes; inject the obtained mixture into a 20 mL syringe for spinning to obtain a composite diaphragm.

[0200] (3) The obtained composite membrane was vacuum dried at 70°C for 12 h to remove the residual solvent; finally, the membrane was hot-pressed at 140°C for 1 h at a pressure of 200 Pa to obtain a boehmite-modified polyacrylonitrile membrane (boehmite / PAN membrane).

[0201] Comparative Example 4

[0202] The commercial separator Celgard-2325 was used as Comparative Example 4.

[0203] Comparative Example 5

[0204] The commercial separator Celgard-2500 was used as Comparative Example 5.

[0205] Table 1 Thickness, porosity, liquid absorption, tensile strength and thermal shrinkage of the membranes prepared by different methods

[0206]

[0207] From Table 1, it can be seen that the porosity of the nanofiber diaphragm prepared by the present invention is between 40% and 60%, and the liquid absorption rate of the electrolyte is higher than that of the commercial polyolefin diaphragm and the related composite diaphragms with thermal closure function of Comparative Examples 1-3. The reason is that the nanofiber diaphragm prepared by the present invention has natural nano-network pores, which has a large porosity, a large specific surface area, and a strong electrolyte absorption. In terms of tensile properties, the commercial polyolefin diaphragms (Comparative Examples 4 and 5) have large differences in transverse and longitudinal tensile strength due to defects in their preparation process, and the transverse tensile properties are too low. Comparative Example 2 is a modified coated polyolefin diaphragm, which also has the same problem. The tensile properties of Comparative Example 1 are significantly higher than those of Comparative Example 3, which reflects that cellulose materials have strong mechanical tensile properties as diaphragms. The nanofiber membrane prepared by the present invention has excellent tensile properties. The dynamically cultured membrane has only a small difference in transverse and longitudinal tensile properties, and its tensile properties are higher than those prepared by static culture. Nanocellulose has naturally excellent thermal stability. The membrane prepared by the present invention has almost no shrinkage at 180°C for 30 minutes, while commercial polyolefin membranes (Comparative Examples 4 and 5) have severe shrinkage, and Comparative Examples 1-3 also have shrinkage to varying degrees.

[0208] Table 2 AC impedance values ​​of diaphragms prepared by different methods at different temperatures (1000Hz)

[0209]

[0210] It can be seen from Table 2 that compared with the batteries prepared from the commercial diaphragms of Comparative Examples 4 and 5, the impedance of the diaphragms prepared by the present invention at 25°C is lower than that of the commercial diaphragms. When the temperature is raised to 80°C, it shows a very large impedance, indicating that at this temperature, the thermoreversible material in the diaphragm expands and blocks the pores, closing the ion transmission channels of the diaphragm. When it returns to room temperature, the thermoreversible material shrinks, restoring the pore structure of the diaphragm, and its impedance is restored to the initial level. The impedance values ​​of the commercial diaphragms (Comparative Examples 4 and 5) do not change at different temperatures. It shows that the diaphragm prepared by the present invention has a thermoreversible closed-pore effect, which ensures the safety of the battery.

[0211] Table 3 Electrochemical and battery performance of membranes prepared by different methods

[0212]

[0213] As shown in Table 3, the bulk resistance of the diaphragm prepared by nanofibers is lower than that of the commercial polyolefin diaphragm and the composite diaphragms with thermal closure function related to Comparative Examples 1-3. Compared with Table 1, it can be seen that the impedance is positively correlated with its thickness. The thickness of the single-layer nanofiber diaphragm is smaller and its impedance is also the smallest; the electrochemical window of all diaphragms within 4V is relatively stable. It is worth noting that the electrochemical window of the diaphragm prepared by the dynamic drum is higher than 5V; all the prepared diaphragms are assembled into batteries. It can be seen that the diaphragm prepared by the present invention has good coulombic efficiency and capacity retention rate (100 times of charge and discharge under 2C rate conditions) of the first charge and discharge, which are higher than the diaphragms prepared in the comparative examples, especially the diaphragm prepared by the dynamic drum method, whose first charge and discharge efficiency reaches 99%, and the capacity retention rate after 100 charge and discharge cycles is above 95%.

Claims

1. A nanocellulose separator with reversible thermal closure performance, characterized in that: The diaphragm is a single-layer or multi-layer structure composite membrane, including a composite layer with a reversible thermal closure function and a nanocellulose membrane; wherein the composite layer is obtained by in-situ composite of a thermally reversible material and nanocellulose.

2. The nanocellulose membrane according to claim 1, characterized in that: The thermally reversible material is a thermally expandable microsphere having a shell-core structure and having the function of thermal expansion and contraction.

3. The nanocellulose membrane according to claim 2, characterized in that: The material of the shell is at least one of polyethylene, polypropylene, ethylene propylene copolymer, acrylonitrile, methyl methacrylate, polystyrene, butyl acrylate, polyvinylidene chloride, butadiene-styrene-(methyl)acrylate copolymer, isophorone diisocyanate, toluene diisocyanate, and diphenylmethane diisocyanate; the material of the core is C5-C9 alkane or cycloalkane.

4. The nanocellulose membrane according to claim 2, characterized in that: The particle size of the heat-expandable microspheres is in the range of 1-10 μm.

5. The nanocellulose membrane according to claim 1, characterized in that: The reversible thermal closure temperature range of the thermally reversible material is 60-150°C.

6. The nanocellulose membrane according to claim 1, characterized in that: The mass concentration of the thermal reversible material in the composite layer is 0.1%-2%.

7. The nanocellulose membrane according to claim 1, characterized in that: The nanocellulose is at least one of microcrystalline nanocellulose, plant nanocellulose, bacterial nanocellulose and animal nanocellulose.

8. The nanocellulose membrane according to claim 1, characterized in that: The membrane also includes a flame retardant coating.

9. A method for preparing a nanocellulose membrane with reversible thermal closure performance, comprising the following steps: (1) preparing a single-layer or multi-layer composite membrane by static in-situ fermentation, dynamic in-situ horizontal drum fermentation, fiber homogenization filtration or membrane patching; (2) The obtained single-layer or multi-layer composite membrane is processed by mechanical extrusion and hot pressing and drying to obtain a nanocellulose membrane with reversible thermal closure performance.

10. Use of the nanocellulose separator with reversible thermal closure function as claimed in claim 1 in liquid lithium batteries, semi-solid lithium batteries or all-solid lithium batteries.

Citation Information

Patent Citations

  • Thermal shutdown heat-resistant high-safety coated and modified membrane and preparation method thereof

    CN108550766A

  • Preparation method of novel high-security polyolefin membrane

    CN108878738A

  • A diaphragm with reversible thermal shutdown properties, its preparation method and application

    CN111653716B

  • Polyolefin-cellulose composite diaphragm and preparation method thereof

    CN112952295A

  • A boehmite-modified polyacrylonitrile reversible thermally shut-off lithium-ion battery separator, its manufacturing method and application

    CN114976487B